Dynamic public perceptions of emerging infectious diseases: A longitudinal study of the H1N1 pandemic - (:unkn) unknown (My University, 2025)
In a currently funded SNSF research project, we are investigating public perceptions of emerging infectious diseases (EIDs) in the Swiss population, focusing on the origins, transmission, and protective measures related to the case of avian influenza. During the initial data collection phase of the project (a large-scale survey), the world unexpectedly experienced an outbreak of a new strain of influenza, H1N1. This outbreak was subsequently declared a pandemic by the World Health Organization (WHO), and unfolded in a much-publicized manner between May and December 2009. We seized this unique opportunity to collect additional data on H1N1. We collected or plan to collect several sets of data at different points in time. We apply for a 12-month extension of the original project to analyze and publish these additional data sets. In the proposal, we recapitulate our original research questions and show that the planned analysis of the additional H1N1 data contributes to answering those questions. We describe progress in our own current research and publications and manuscripts that have been produced. The planned research will consist of three sets of analyses. First (Study 1), we will analyze two waves of surveys (total n = 302) on perceptions of H1N1 collected in May and December 2009. Next (Study 2) we will analyze two waves of interviews (total n = 75) on perceptions of H1N1 collected in May and December 2009. Finally (Study 3), we will analyze results from a survey on H1N1 that will be conducted in March 2010 (planned n = 300). These data will allow us to study the evolution of the H1N1 pandemic from its outbreak to its aftermath using multiple methods. The planned analyses on the unprecedented H1N1 outbreak have the potential to create unique scientific knowledge about how the public perceives the salience, origins, transmission and prevention of H1N1, especially from a temporal perspective. The analyses may also augment the validity and generalizability of our avian flu results, thereby strengthening potential implications for managing the risks posed by EIDs in general. Moreover, our analyses may contribute important insights to ongoing research in social psychology of disease threat. The research group will seek publication of findings in peer-reviewed international journals in the fields of social psychology and public health. Study results will also be made available to interested organizations, the media and the public.
Keywords: social representations; emerging infectious diseases; H1N1 pandemic influenza